Long-term survival after paclitaxel plus platinum-based combination chemotherapy for extraovarian peritoneal serous papillary carcinoma: is it different from that for ovarian serous papillary cancer?. Issue 2 (1st March 2006) - Ayhan, A.; Taskiran, C.; Yigit-Celik, N.; Bozdag, G.; Gultekin, M.; Usubutun, A.; Guler, N.; Yuce, K.
Abstract : The purpose of this study was to compare the effect of paclitaxel plus platinum-based chemotherapy in the treatment of extraovarian peritoneal serous papillary carcinoma (EPSPC) and ovarian serous papillary cancer (OSPC). Only the patients treated with initial surgery plus postoperative adjuvant chemotherapy and having FIGO stage IIIC disease with omental and/or peritoneal involvement were analyzed. Thirty-two patients with EPSPC and 43 with OSPC were included in this study. The median age, mean CA-125, and volume of ascitis were higher in patients with EPSPC. There was no significant difference between the two groups with respect to other prognosticators. The median overall survival (OS) durations were 30 months (95% CI 24.8–35.3) in patients with EPSPC and 28 months (95% CI 21.1–34.9) in those with OSPC ( P = 0.35). The 3-year OS rates in the patients and controls were 28% and 31%, respectively ( P = 0.84). In patients with EPSPC, only optimal cytoreduction was significantly related to progression-free survival and OS durations as a prognostic factor. In the EPSPC group, 65.5% of the patients (19/29) had lymphatic involvement, compared to 88.4% (38/43) in the OSPC group ( P = 0.02). As an adjuvant therapy, the paclitaxel plus platinum-based combination regimen had similar effects on survival in the EPSPC and OSPC groups.